1988
DOI: 10.3109/00365548809032496
|View full text |Cite
|
Sign up to set email alerts
|

A Family Cluster of Legionella pneumophila Infections

Abstract: Three members of one single family of 4, the father, a son and a daughter, showed seroconversion against Legionella pneumophila serogroup 1 (Lp SG1). The son had a severe pneumonia, whereas the father and the daughter did not develop any other illness than mild and transient fever. A fourth member, the mother, remained seronegative. Lp SG1 was detected by a direct immunofluorescence test in water samples from the shower at home, in tap water in the family's butcher shop, and in condensation water from the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Only few of these bacteria species cause infections in humans [36][37][38][39][40][41][42][43][44]. Most important are Legionella pneumophilae and Pseudomonas aeruginosa which may cause severe infections, not only in ill patients but also in normal persons especially elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Only few of these bacteria species cause infections in humans [36][37][38][39][40][41][42][43][44]. Most important are Legionella pneumophilae and Pseudomonas aeruginosa which may cause severe infections, not only in ill patients but also in normal persons especially elderly.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that more than 100 different bacteria was found in the same biofilm by genome sequencing [17]. Only few of these bacteria species causes infections in humans [36][37][38][39][40][41][42][43][44]. Most important are Legionella pneumophilae and Pseudomonas aeruginosa which may cause severe infections, not only in ill patients but also in normal persons especially elderly.…”
Section: Introduction mentioning
confidence: 99%
“…In another study, Castellani Pastoris et al (5) reported that seroconversion against L. pneumophila sg 1 was found in three of the four family members; the father and daughter developed an influenza-like infection, but the son developed serious pneumonia. Legionella pneumophila sg 1 was present in the showerhead water and running water of the family's residence, as well as in the ventilation circuits of the refrigerator located in the family's shop.…”
mentioning
confidence: 95%